2014
DOI: 10.1007/s12013-014-9827-5
|View full text |Cite
|
Sign up to set email alerts
|

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is an aggressive malignancy that has a poor prognosis. 5-Fluorouracil (5-FU) is a first line chemotherapeutic medication used in the treatment of gallbladder cancer; however, the efficacy is below satisfactory. Icariin is a natural compound that is conventionally reported to have activity against a variety of cancers. This study was carried out to investigate the anti-cancer effect of icariin in CRC cells and to determine whether the compound can enhance the antitumour activity of 5-FU.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In contrast, icariin was able to abrogate the effects of LPS on neuroinflammation, lung inflammation, osteoclast differentiation and bone resorption via decreasing NF-κB activity (23,49,54,55). It has also been reported that icariin inhibits NF-κB activity in a wide range of cancerous cells (56)(57)(58)(59). The results of the present study demonstrated that icariin suppresses the cytokine-induced activation of NF-κB in rat pancreatic β cells.…”
Section: Discussionsupporting
confidence: 41%
“…In contrast, icariin was able to abrogate the effects of LPS on neuroinflammation, lung inflammation, osteoclast differentiation and bone resorption via decreasing NF-κB activity (23,49,54,55). It has also been reported that icariin inhibits NF-κB activity in a wide range of cancerous cells (56)(57)(58)(59). The results of the present study demonstrated that icariin suppresses the cytokine-induced activation of NF-κB in rat pancreatic β cells.…”
Section: Discussionsupporting
confidence: 41%
“…A previous research disclosed that the drug target of ICA might be related to the increase of cAMP/cGMP ratio (ZHU and LOU, 2006). The related researches uncovered that ICA exerted the antitumor functions mainly in inducing apoptosis and differentiation, prohibiting invasion and metastasis, restraining angiogenesis, and reducing toxicity of radiotherapy and chemotherapy (Yang et al, 2015;Gui et al, 2018;Shi et al, 2014). Among these, the mechanism of SPARC involved in tumorigenesis includes inducing differentiation, inhibiting invasion and metastasis, and restraining angiogenesis of cancer cells (Chen et al, 2012;Ma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Icariin has also been reported to exhibit anticancer activity against various cancer cell lines. It mainly induced apoptosis via ROS generation and inhibiting NF-КB translocation into nucleus 53 , 54 . Chemical profile of Icariin treated animals demonstrated that Icariside II is the major pharmacological active form of Icariin in vivo 50 , 52 , 55 .…”
Section: Natural Sourcesmentioning
confidence: 99%